Connection between Suicidal Ideation, Life Meaning, and Leisure Time Activities. Issue 6 (3rd June 2017) - Aviad-Wilchek, Yael; Ne'eman-Haviv, Vered; Malka, Michal
ABSTRACT: This study is an examination of the links between adolescent suicidal ideation, life meaning, and the ways they spend their leisure time. The sample consisted of 450 students aged 15–18. Findings showed a significant negative correlation between suicidal ideation and sense of life meaning, encompassing factors such as age and gender. Adolescents with involvement in social activities demonstrated lower levels of suicidal ideation (total score), and lower levels of depression and anxiety, than the other two groups. The study discusses the research and practical implications of these findings. The findings suggest the possibility of establishing prevention, intervention, and therapy programs for adolescents based on life meaning.